Ekspresi Protein Gen p53 yang Bermutasi pada Jaringan Sediaan Blok Parafin Kanker Paru Karsinoma Bukan Sel Kecil - ARIF R HANAFI; ELISNA SYAHRUDDIN; AHMAD HUDOYO (Indonesian Journal of Cancer, 2010)
The tumor supressor gen p53 mutation encodes a protein that inhibits programmed cell death (apoptosis). The protein is expressed in basal cells in normal human epithelium, but no data are available on the frequency or clinical importance of its expression in carcinoma. We studied p53 mutation protein expression in post surgery tissues of patients with non-small cell lung carcinoma (NSCLC) and evaluated the correlation between protein expressions with prognosis of diseases. We have performed a retrospective study using 43 parafin block samples of NSCLC patients who were underwent surgery in Persahabatan Hospital during 1997 to 2008. The p53 mutation protein expression were analyzed by immunohystochemical method using a monoclonal antibody specific for p53 mutation protein. The possibility that p53 mutation expression correlated with survival was investigated with the log-rank test Kaplan Meier. Patients characteristic we found male 25/43 (58.1%) female 18/43 (41.9%) with mean age 56.19 + 8.3 y.o and mostly age 40 to 60 y.o 33/43 (76.7%). Number of smoker patiens were 31/43 (72.1%). We also detected p53 mutation protein in 16/43 (37,2%) in NSCLC tissues. Regarding histopatology types were 9/18 (50%) in squamous-cell carcinomas and 7/25 (28%) in adenocarcinomas. The corellation between positive p53 mutation protein expressions with pathological staging was significant p 0,004, according to T status T1-T2 62,5% and T3-T4 23,8% have had positive p53 mutation protein. Favorable prognostic significance of p53 mutation in patients with NSCLC stage I II, patients in the positive p53 mutataion survived longer than those in negative with respective median survival durations 28 and 18 months p 0,019. Adenocarcinomas type with p53 mutation have had median survival 11 months compared with squamose cell carcinomas 14 months.